Disentangling the Role of Working Memory in Parkinson’s Disease - Salmi, Juha; Ritakallio, Liisa; Fellman, Daniel; Ellfolk, Ulla; Rinne, Juha O.; Laine, Matti (Frontiers in Aging Neuroscience, 2020)
Working memory represents a core cognitive function with major striatal contribution, and thus working memory deficits, commonly observed in Parkinson's disease, could also relate to many other problems in Parkinson's disease patients. Our online study aimed to determine the subdomains of working memory that are particularly affected in Parkinson's disease, and to clarify the links between working memory and everyday cognitive deficits, other executive functions, psychiatric and Parkinson's disease symptoms, as well as early cognitive impairment. Fifty-two mild-to-moderate Parkinson's disease patients and 54 healthy controls performed seven working memory tasks tapping selective updating, continuous monitoring, or maintenance of currently active information. Self-ratings of everyday cognition, depression and apathy symptoms, as well as screenings of global cognitive impairment were also collected. The data were analysed using structural equation modelling. Of the three working memory domains, only selective updating was directly predictive of Parkinson's disease group membership. More widespread working memory deficits were observed only in relation to global cognitive impairment in Parkinson's disease patients. Self-rated everyday cognition or psychiatric symptoms were not linked to working memory performance but correlated with each other. Our findings suggest that working memory has a rather limited role in the clinical manifestation of Parkinson's disease. Nevertheless, due to its elementary link to striatal function, the updating component of working memory could be a candidate for a cognitive marker of Parkinson's disease also in patients who are otherwise cognitively well-preserved.